Photodegradation of norfloxacin adsorbed on clay and carbon-clay nanomaterials: an evaluation based on antimicrobial tests - Zelaya Soulé, María Emilia (2022)
The antibiotic norfloxacin was adsorbed on clay and carbon-clay nanocomposites (MD-210 and MDac3-210-500, synthesized by hydrothermal carbonization of dextrose) but maintained its antimicrobial activity once adsorbed. To degrade it, direct (DP) and indirect (IP, with sulfate radicals) photolysis were performed. Antimicrobial activity tests were performed to evaluate the degradation generated. There were no significant differences between DP and IP for unabsorbed norfloxacin solution. The IP treatment caused a loss of antibiotic activity in all cases. For DP, the carbon samples showed better results than those of clay, evidencing the importance of oxygenated carbonaceous groups in the photolysis of norfloxacin.